Social Power Delineates in the Novel This Earth of Mankind (1996) Translated by Max Lane - Marasno, Risal; Rijal, Andi Samsu; Halim, Nur Muthmainnah; Kamal, Alfiandy (ASHLITION : Ash-Shahabah English Literature, Linguistics, & Education, 2024)
This study aimed to analyze how social power was depicted in the novel This Earth of Mankind (1996) translated by Max Lane and how the relationship among characters represents social power by using French and Raven's theory (1959) of social power. This research used descriptive-qualitative. This study focused on the dialogues among characters. The results of this study showed that 2 data points on the reward power, 4 data points on the coercive power, 18 data points on the legitimate power, 14 data points on the referent power, and 13 data points on the expert power. In representing social power, the characters in the novel describe various dynamics of social power. The representation of social power shows that the relationship among characters affects the dynamics of social class and social interaction among characters. Additionally, economic power highlights the character's dependence on material resources, which are often tools of control and domination. The social power did not only influence individuals separately but also shapes social structures and hierarchies in the novel, reflecting complex and dynamic social realities.